170k views
4 votes
Solve the equation. check your answer.
-14 = -4(9x - 1)​

2 Answers

2 votes

Answer :

➠ -14 = -4(9x - 1)

Multiplying by -1 on both sides,

we ge
t

➠ 14 = 4(9x - 1)

➠ 14 = (4 × 9x) - (4 × 1)

➠ 14 = 36x - 4

➠ 36x = 14 + 4

➠ 36x = 18

➠ x = 18/36

➠ x = 1/2

x = 0.5

Hope It Helps!

User Julienduchow
by
5.6k points
2 votes

Answer:

x = 0.5

Explanation:

First, distribute -4 to the parentheses:

-14 = -4(9x - 1)​

-14 = -36x + 4

Subtract 4 from both sides:

-18 = -36x

Divide each side by -36

0.5 = x

x = 0.5

User Lesleh
by
6.3k points